(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article deals with the issues of professionalization of crafts among students of the "preschool education" direction, on improving the professionogram of future teachers on the application of national crafts and applied arts in universities. The analysis of scientific research works of foreign and domestic scientists is also given, organizational and methodological criteria for the professional development of future educators are discussed.